(untitled) (Research Journal, 2024)
The study explores the impact of Triguna Prakriti, as elucidated in Chapter 14 of the Bhagavad Gita, on the behavior of teachers and students. Drawing on interpretative research methodology, the research delves into the three qualities of nature - Sattva, Rajas, and Tamas - and their manifestation in human psychology. The reflective study aims to interpret the Triguna Prakriti in relation to human behavior, specifically focusing on teachers and students. Through a hermeneutic approach, the study examines the nuances of each Gunas and their influence on individuals’ actions and attitudes. The Bhagavad Gita serves as a foundational text, providing insights into the nature of human behavior and the role of teachers in guiding students towards self-realization. By analyzing the text and its interpretations, the study sheds light on the intricate relationship between Triguna Prakriti and the behavior of teachers and students.